2012
DOI: 10.5603/nmr-18726
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of normal myocardial perfusion spect with positive coronary angiography

Abstract: We observed that the normal SPECT with positive ECG pattern is infrequent and has a very good prognostic value However, the long-term survival among a patient cohort with a normal exercise SPECT study is influenced by the number of concomitant CAD risk factors. We conclude that there is an importance of modifying CAD risk factors among patients with a normal SPECT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Male sex, older age and typical angina were predictors of CAD. In another report, Kostkiewicz and Szot [25] found that in patients with normal 99mTc MIBI SPECT perfusion images (45 patients underwent coronary angiography). One of the 20 women had 40% stenosis of the left main coronary artery, 6 had single and 14 had 2-vessel disease.…”
Section: Discussionmentioning
confidence: 94%
“…Male sex, older age and typical angina were predictors of CAD. In another report, Kostkiewicz and Szot [25] found that in patients with normal 99mTc MIBI SPECT perfusion images (45 patients underwent coronary angiography). One of the 20 women had 40% stenosis of the left main coronary artery, 6 had single and 14 had 2-vessel disease.…”
Section: Discussionmentioning
confidence: 94%